Centrum Doskonałości im. Jeana Monneta. Unia Europejska w roli gwaranta i promotora praw podstawowych - Kornobis-Romanowska, Dagmara (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Jean Monnet Centre of Excellence (CEJM), The European Union as a Guarantor and Promoter of Fundamental Rights was established at the University of Wroclaw by the decision of European Commission for the years 2014–2017. It is based on the Jean Monnet Chair, as a point of competence and knowledge on European Union subjects. It is part and highest level of the Jean Monnet program, initiated in 1989 to stimulate teaching, research and reflection on the European integration not only within the EU but also globally, outside of the European Union. Currently, there are nearly 200 Centres of Excellence operating worldwide. The Centre at the University of Wroclaw is the first established in Poland in the field of studies and research on EU law. The Centre is directed by Prof. Dagmara Kornobis-Romanowska.
Keywords: Centrum Doskonałości im. Jeana Monneta; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego